A hydrophilic porous membrane and preparation method thereof

Through the cross-linking reaction and blending method of polyamine compounds and β-cyclodextrin, a porous membrane with long-lasting hydrophilicity, high throughput, high retention and anti-pollution properties was prepared, which solved the porosity of existing membrane materials. Problems of poor stability of plugging and modifiers.

CN115646216BActive Publication Date: 2025-02-11GUIZHOU MATERIAL IND TECH INSTITUE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211388791.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-08
Publication Date
2025-02-11
Estimated Expiration
2042-11-08

AI Technical Summary

Technical Problem

In the existing membrane separation technology, polymer membrane materials are prone to pore blockage and contamination due to hydrophobicity, and the blended modifier has poor stability in the membrane, which affects the long-lasting hydrophilicity and performance of the membrane.

Method used

By crosslinking the polyamine compound with β-cyclodextrin and blending it with porogenic agent and membrane-forming polymer, a uniform casting film liquid is formed. The porous membrane is prepared by phase conversion method, and the crosslinked product is fixed in the membrane. , improve its lasting hydrophilicity and stability.

Benefits of technology

The film is achieved with a long-lasting hydrophilicity, improving the film's flux, retention and anti-pollution properties, and avoiding the problem of poor stability of blended modifiers in the film.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application discloses a method for preparing a hydrophilic porous membrane, wherein a polyamine compound and β-cyclodextrin are simultaneously introduced through a one-step blending and cross-linking process to prepare a hydrophilic porous membrane, and hydrophilic modification is achieved during the membrane preparation. The cross-linked product of the polyamine compound and β-cyclodextrin has excellent hydrophilicity and is insoluble in water, and an interpenetrating network structure is formed between the cross-linked structure and the hydrophobic polymer to prevent gradual loss and peeling during use; the introduction of a polyamine compound makes the membrane surface close to electrical neutrality, thereby improving the anti-pollution performance of the membrane. Therefore, the prepared membrane not only maintains the mechanical strength of the traditional polymer membrane, but also has the advantages of high flux, high interception performance, good anti-pollution performance and lasting hydrophilicity. The present application also discloses a hydrophilic porous membrane, which can be used in industrial fields such as deep purification of drinking water, oil-water separation, sewage treatment, protein and drug purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of separation membranes, and specifically relates to a hydrophilic porous membrane and a preparation method thereof. Background Art

[0002] Membrane separation technology is an economical and efficient separation method. Currently, the vast majority of membrane products are based on organic polymer membranes. Most polymer materials (such as PVC, PVDF, PES, PSF, etc.) are highly hydrophobic. During use, the membrane pores are easily blocked, causing membrane pollution and affecting the operation of the membrane assembly. Hydrophilic modification of membrane materials can effectively reduce the occurrence of membrane pollution.

[0003] Blending modification is the simplest and most effective method to improve membrane performance. It can make the membrane have the comprehensive advantages of blended materials, without affecting the physical and chemical properties of the materials. It is relatively simple, low-cost, and easy to industrialize. It is the current mainstream modification method. Traditional blending modifiers such as small molecule additives (such as LiCl) or water-soluble polymers (such as PEG or PVP) are very soluble in water. They mainly act as pore-forming agents in the membrane making process. Only a small part of them can be retained in the membrane, and they are easy to gradually lose from the membrane material during use. There are also some high molecular polymers (such as PVA, PAN, EVOH, etc.) that have certain hydrophilicity but are insoluble in water. For hydrophilic modification, however, due to the poor compatibility of the system, defective pores are easily generated, resulting in reduced mechanical properties and interception performance of the membrane. In addition, the blending amount cannot be too much. Due to the limited hydrophilicity of these blending substances themselves, the hydrophilic modification effect of the product is ultimately limited.

[0004] Therefore, it is necessary to provide a hydrophilic porous membrane and a preparation method thereof to solve the above problems. Summary of the invention

[0005] The purpose of the embodiment of the present application is to provide a hydrophilic porous membrane and a preparation method thereof, wherein a hydrophilic polyamine compound and β-cyclodextrin are cross-linked by a cross-linking agent, and then a porogen and a membrane-forming polymer material are added to blend in one step to obtain a uniform casting solution, and a polymer porous membrane is prepared by a phase inversion method. The hydrophilic polyamine compound and β-cyclodextrin are simultaneously fixed to the membrane material body and the membrane surface by a cross-linking agent, thereby preventing them from gradually losing due to water solubility during the use of the membrane, improving the durable hydrophilicity of the membrane, and the cross-linked macromolecules are not easily eluted, and can exist in the membrane for a long time, effectively solving the problem of poor stability of the blending modifier in the membrane. In addition, cross-linking eliminates interface defects and improves interception performance, and forms an interpenetrating network structure with the hydrophobic polymer to prevent peeling. The prepared porous membrane has the advantages of high flux, high interception performance, good anti-pollution performance and durable hydrophilicity.

[0006] In order to solve the above technical problems, this application is implemented as follows:

[0007] A method for preparing a hydrophilic porous membrane comprises the following steps:

[0008] S1: Dissolve 1-2 parts of a polyamine compound and 1-10 parts of β-cyclodextrin in a solvent according to their mass fractions, and stir under heating conditions until dissolved; add a catalyst under stirring, and drop a crosslinking agent to carry out a crosslinking reaction; then add a porogen and a membrane-forming polymer, continue stirring and heating for 4-8 hours, and obtain a casting solution after vacuuming and degassing;

[0009] S2: the casting solution is coated by a scraper or extruded by a hollow fiber spinneret, and then immersed in a coagulation bath to cool and solidify after passing through an air gap to form a primary membrane;

[0010] S3: Soaking the primary membrane in deionized water for 48 hours, and then drying it naturally at room temperature to obtain a hydrophilic porous membrane.

[0011] Preferably, in step S1, the mass fraction of the solvent is 48-85.5 parts, the mass fraction of the cross-linking agent is 0.5-5 parts, the mass fraction of the porogen is 2-10 parts, and the mass fraction of the membrane-forming polymer is 10-25 parts.

[0012] Preferably, the volume of the catalyst accounts for 0-1% of the volume of the solvent.

[0013] Preferably, the polyamine compound is any one of triethylenetetramine, tetraethylenepentamine, polyethylene polyamine, and polyethyleneimine polymer; the solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the catalyst is any one of concentrated hydrochloric acid, concentrated sulfuric acid, or p-toluenesulfonic acid; the cross-linking agent is any one of glyoxal, glutaraldehyde, and epichlorohydrin; the porogen is any one of polyethylene glycol and polyvinyl pyrrolidone, or a mixture of two of the two; and the membrane-forming polymer is any one of polyvinylidene fluoride, polyvinyl chloride, polysulfone, and polyether sulfone.

[0014] Preferably, in step S1, the heating temperature is 60-80° C. and the cross-linking reaction time is 0.5-2 h.

[0015] Preferably, in step S2, the coagulation bath is deionized water at 20-60°C.

[0016] The present application also provides a hydrophilic porous membrane, which is prepared by the above-mentioned preparation method.

[0017] Preferably, the hydrophilic porous membrane is a flat membrane or a hollow fiber membrane.

[0018] The present application prepares a hydrophilic porous membrane by simultaneously introducing a polyamine compound and β-cyclodextrin through a one-step blending and cross-linking, thereby achieving a simultaneous hydrophilic modification during membrane preparation. The cross-linked product of the polyamine compound and β-cyclodextrin has excellent hydrophilicity and is insoluble in water. An interpenetrating network structure is formed between the cross-linked structure and the hydrophobic polymer to prevent gradual loss and peeling during use; the introduction of a polyamine compound makes the membrane surface close to electrical neutrality, thereby improving the anti-pollution performance of the membrane. Therefore, the prepared membrane not only maintains the mechanical strength of the traditional polymer membrane, but also has the advantages of high flux, high interception performance, good anti-pollution performance and lasting hydrophilicity. The hydrophilic porous membrane prepared in the present application can be used in industrial fields such as deep purification of drinking water, oil-water separation, sewage treatment, protein and drug purification. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0020] A method for preparing a hydrophilic porous membrane comprises the following steps:

[0021] S1: Dissolve 1-2 parts of polyamine compound and 1-10 parts of β-cyclodextrin in a solvent according to their mass fractions, and stir under heating conditions until dissolved; add a catalyst under stirring, and drop a cross-linking agent to carry out a cross-linking reaction; then add a porogen and a membrane-forming polymer, continue stirring and heating for 4-8 hours, and obtain a casting solution after vacuuming and degassing.

[0022] S2: the casting solution is coated by a scraper or extruded by a hollow fiber spinneret, and then immersed in a coagulation bath to cool and solidify after passing through an air gap to form a primary membrane;

[0023] S3: Soaking the primary membrane in deionized water for 48 hours, and then drying it naturally at room temperature to obtain a hydrophilic porous membrane.

[0024] In step S1, the mass fraction of the solvent is 48-85.5 parts, the mass fraction of the crosslinking agent is 0.5-5 parts, the mass fraction of the porogen is 2-10 parts, the mass fraction of the membrane-forming polymer is 10-25 parts, and the volume of the catalyst accounts for 0-1% of the volume of the solvent.

[0025] The polyamine compound is any one of triethylenetetramine, tetraethylenepentamine, polyethylene polyamine, and polyethyleneimine polymer; the solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the catalyst is any one of concentrated hydrochloric acid, concentrated sulfuric acid, or p-toluenesulfonic acid; the cross-linking agent is any one of glyoxal, glutaraldehyde, and epichlorohydrin; the porogen is any one of polyethylene glycol and polyvinyl pyrrolidone or a mixture of two of the two; and the membrane-forming polymer is any one of polyvinylidene fluoride, polyvinyl chloride, polysulfone, and polyether sulfone.

[0026] In the step S1, the heating temperature is 60-80° C. and the cross-linking reaction time is 0.5-2 h.

[0027] In step S2, the coagulation bath is deionized water at 20-60°C.

[0028] In the present application, a hydrophilic polyamine compound is cross-linked with β-cyclodextrin through a cross-linking agent. The cross-linked product is soluble in a solvent but insoluble in water. It is then blended with a porogen and a polymer material in one step ("one-pot method") to obtain a uniform casting liquid. The casting liquid is prepared and modified at the same time, and a polymer porous membrane is obtained by a phase inversion method. The operation method is simple.

[0029] Furthermore, by introducing polyamine compounds, the degree of negative charge on the membrane surface is reduced, making the membrane surface close to electrical neutrality, and weakening the interaction between the membrane and the charged pollutants in the water. In addition, cross-linking introduces numerous hydrophilic hydroxyl groups to form hydrogen bonds with water molecules, forming a strong hydration layer on the membrane surface, which acts as a physical and energy barrier and can significantly improve the membrane's anti-pollution performance.

[0030] β-cyclodextrin has a hollow shape, and the internal hydrophobic cavity makes it compatible with polymers. The numerous hydroxyl groups on the outside give it good hydrophilicity. Through the cross-linking reaction, the polyamine compound and β-cyclodextrin are fixed to the membrane body and the membrane surface at the same time, improving the long-term hydrophilicity of the membrane; at the same time, the cross-linked product is insoluble in water and can exist in the membrane for a long time. The cross-linked structure and the hydrophobic polymer form an interpenetrating network structure to prevent peeling during use. In addition, cross-linking effectively eliminates the problem of reduced interception performance caused by defects caused by blending. Therefore, the prepared hydrophilic porous membrane not only maintains the mechanical strength of traditional polymer membranes, but also has the advantages of high flux, high interception performance, good anti-pollution performance and long-lasting hydrophilicity. The prepared hydrophilic porous membrane can be used in separation processes such as deep purification of drinking water, oil-water separation, sewage treatment, protein and drug purification.

[0031] The present application also provides a hydrophilic porous membrane, which is prepared by the above-mentioned preparation method. The hydrophilic porous membrane is a flat membrane or a hollow fiber membrane.

[0032] Example 1

[0033] (1) 1 g of triethylenetetramine and 1 g of β-cyclodextrin were dissolved in 71.5 g of solvent N,N-dimethylacetamide, and mechanically stirred at 80° C. until dissolved. Then, 0.35 ml of catalyst hydrochloric acid was added under stirring, and 3.5 g of cross-linking agent glutaraldehyde was slowly added dropwise to react for 0.5 h. Then, 8 g of polyethylene glycol and 15 g of polyvinylidene fluoride were added and continued to stir and heat for 6 h. Vacuum degassing was performed to obtain a uniform casting solution.

[0034] (2) coating the casting solution with a scraper, leaving it in the air for 30 seconds, and then immersing it in deionized water for curing to obtain a primary film;

[0035] (3) The primary membrane was immersed in deionized water for 48 hours and dried naturally at room temperature to obtain a hydrophilic porous membrane.

[0036] Example 2

[0037] (1) 1 g of tetraethylenepentamine and 2 g of β-cyclodextrin were dissolved in 70.5 g of solvent N,N-dimethylacetamide, and mechanically stirred at 80° C. until dissolved. Then, 0.35 ml of catalyst sulfuric acid was added under stirring, and 3.5 g of cross-linking agent glutaraldehyde was slowly added dropwise to react for 0.5 h. Then, 8 g of polyethylene glycol and 15 g of polyvinylidene fluoride were added and continued to stir and heat for 6 h. Vacuum degassing was performed to obtain a uniform casting solution.

[0038] (2) coating the casting solution with a scraper, leaving it in the air for 30 seconds, and then immersing it in deionized water for curing to obtain a primary film;

[0039] (3) The primary membrane was immersed in deionized water for 48 hours and dried naturally at room temperature to obtain a hydrophilic porous membrane.

[0040] Example 3

[0041] (1) 1.5 g of triethylenetetramine and 4.5 g of β-cyclodextrin were dissolved in 65.5 g of solvent N,N-dimethylacetamide, and mechanically stirred at 80° C. until dissolved, and then 0.33 ml of catalyst p-toluenesulfonic acid was added under stirring, and 3.5 g of cross-linking agent glyoxal was slowly added dropwise for 0.5 h, and then 5 g of polyvinyl pyrrolidone and 20 g of polysulfone were added and continued to stir and heat for 6 h, and vacuum degassing was performed to obtain a uniform casting solution;

[0042] (2) coating the casting solution with a scraper, leaving it in the air for 30 seconds, and then immersing it in deionized water for curing to obtain a primary film;

[0043] (3) The primary membrane was immersed in deionized water for 48 hours and dried naturally at room temperature to obtain a hydrophilic porous membrane.

[0044] Example 4

[0045] (1) 2 g of triethylenetetramine and 6 g of β-cyclodextrin were dissolved in 63.5 g of solvent N,N-dimethylacetamide, and mechanically stirred at 80° C. until dissolved. Then, 0.32 ml of catalyst hydrochloric acid was added under stirring, and 3.5 g of cross-linking agent epichlorohydrin was slowly added dropwise to react for 0.5 h. Then, 5 g of polyvinyl pyrrolidone and 20 g of polyether sulfone were added and continued to stir and heat for 6 h. Vacuum degassing was performed to obtain a uniform casting solution.

[0046] (2) coating the casting solution with a scraper, leaving it in the air for 30 seconds, and then immersing it in deionized water for curing to obtain a primary film;

[0047] (3) The primary membrane was immersed in deionized water for 48 hours and dried naturally at room temperature to obtain a hydrophilic porous membrane.

[0048] Example 5

[0049] (1) 2 g of triethylenetetramine and 10 g of β-cyclodextrin were dissolved in 65.5 g of N,N-dimethylformamide solvent, and mechanically stirred at 80° C. until dissolved. Then, 0.33 ml of catalyst hydrochloric acid was added under stirring, and 3.5 g of cross-linking agent glutaraldehyde was slowly added dropwise to react for 0.5 h. Then, 4 g of polyvinyl pyrrolidone and 15 g of polyvinyl chloride were added and stirred and heated for 6 h. Vacuum degassing was performed to obtain a uniform casting solution.

[0050] (2) coating the casting solution with a scraper, leaving it in the air for 30 seconds, and then immersing it in deionized water for curing to obtain a primary film;

[0051] (3) The primary membrane was immersed in deionized water for 48 hours and dried naturally at room temperature to obtain a hydrophilic porous membrane.

[0052] Example 6

[0053] (1) 2 g of polyethyleneimine and 4 g of β-cyclodextrin were dissolved in 71.5 g of solvent N,N-dimethylacetamide, and mechanically stirred at 80° C. until dissolved. Then, 0.35 ml of catalyst hydrochloric acid was added under stirring, and 3.5 g of cross-linking agent glutaraldehyde was slowly added dropwise to react for 0.5 h. Then, 4 g of polyvinyl pyrrolidone and 15 g of polyvinylidene fluoride were added and stirred and heated for 6 h. Vacuum degassing was performed to obtain a uniform casting solution.

[0054] (2) coating the casting solution with a scraper, leaving it in the air for 30 seconds, and then immersing it in deionized water for curing to obtain a primary film;

[0055] (3) The primary membrane was immersed in deionized water for 48 hours and dried naturally at room temperature to obtain a hydrophilic porous membrane.

[0056] Comparative Example 1

[0057] (1) 8 g of polyethylene glycol and 15 g of polyvinylidene fluoride were dissolved in 77 g of N,N-dimethylacetamide solvent, stirred at 80° C. for 6 h, and then vacuumed and degassed to obtain a uniform casting solution;

[0058] (2) coating the casting solution with a scraper, leaving it in the air for 30 seconds, and then immersing it in deionized water for curing to obtain a primary film;

[0059] (3) The primary membrane was immersed in deionized water for 48 hours and dried naturally at room temperature to obtain a porous membrane.

[0060] Comparative Example 2

[0061] (1) 5 g of polyvinyl pyrrolidone and 20 g of polysulfone were dissolved in 75 g of N,N-dimethylacetamide solvent, stirred at 80° C. for 6 h, and then vacuumed and degassed to obtain a uniform casting solution;

[0062] (2) coating the casting solution with a scraper, leaving it in the air for 30 seconds, and then immersing it in deionized water for curing to obtain a primary film;

[0063] (3) The primary membrane was immersed in deionized water for 48 hours and dried naturally at room temperature to obtain a porous membrane.

[0064] The products of Examples 1-6 and Comparative Examples 1-2 were subjected to the following performance tests, respectively. The test results are shown in Table 1:

[0065] (1) Water flux test: Cut a standard size membrane, pre-press it with 25℃ deionized water at 0.15MPa pressure for 30min, then test it at 0.1MPa pressure for 1h, and then calculate the pure water flux per unit area and time, recorded as J w1 (L / m 2 h).

[0066] (2) Hydrophilicity test: The hydrophilicity of the membrane is characterized by measuring the initial water contact angle and the dynamic contact angle within 180 seconds. Generally speaking, the smaller the initial contact angle of the membrane, the stronger the surface hydrophilicity. The dynamic contact angle of the membrane better reflects the dynamic changes of the contact angle between the membrane surface and water. Randomly measure 5 times at different positions on each membrane and take the average value.

[0067] (3) Test of interception performance and anti-pollution performance: Cut a standard size membrane sheet, and after testing the pure water flux, replace the deionized water with a BSA solution with a concentration of 1.0 g / L. Test it at a pressure of 0.1 MPa for 1 h, and calculate the flux of the filtered BSA solution, which is recorded as J. pAt the same time, take the BSA stock solution and the filtrate and measure the absorbance with a UV-visible spectrophotometer to convert the concentration. The stock solution concentration is recorded as c f (gL -1 ), the filtrate concentration is recorded as c p (gL -1 ), the retention rate of membrane for BSA is R = (1-c p / c f )×100; After filtering BSA, the membrane was backwashed and filtered for 30 min, and then the pure water flux after flushing was tested at a pressure of 0.1 MPa. w2 (L / m 2 h). Flux recovery rate FRR = (J w2 / J w1 )×100, and the flux recovery rate is used to characterize the anti-fouling performance of the separation membrane. The higher the flux recovery rate, the better the anti-fouling performance of the membrane.

[0068] Table 1 Membrane performance data of Examples 1-6 and Comparative Examples 1-2

[0069] <![CDATA[J w1 ]]> R FRR Initial contact angle Dynamic contact angle Example 1 2586 96% 92% 71° 74s down to 0° Example 2 3695 97% 95% 68° 65s down to 0° Example 3 986 97% 92% 66° 60s down to 0° Example 4 654 99% 95% 65° 55s down to 0° Example 5 1654 98% 92% 66° 70s down to 0° Example 6 4541 96% 95% 68° 60s down to 0° Comparative Example 1 397 85% 75% 79° 180s down to 67° Comparative Example 2 258 88% 79% 76° 180s down to 52°

[0070] It can be seen from Table 1 that, compared with Comparative Examples 1-2, the hydrophilic porous membrane provided in the present application not only has a significantly improved pure water flux, but also has excellent interception performance, hydrophilicity and anti-pollution performance.

[0071] The embodiments of the present application are described above, but the present application is not limited to the above-mentioned specific implementation modes. The above-mentioned specific implementation modes are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.

Claims

1. A method for preparing a hydrophilic porous membrane, characterized in that: The steps include: S1: Dissolve 1-2 parts of a polyamine compound and 1-10 parts of β-cyclodextrin in a solvent according to their mass fractions, and stir under heating conditions until dissolved; add a catalyst under stirring, and drop a crosslinking agent to carry out a crosslinking reaction; then add a porogen and a membrane-forming polymer, continue stirring and heating for 4-8 hours, and obtain a casting solution after vacuuming and degassing; S2: the casting solution is coated by a scraper or extruded by a hollow fiber spinneret, and then immersed in a coagulation bath to cool and solidify after passing through an air gap to form a primary membrane; S3: soaking the primary membrane in deionized water for 48 hours, and then drying it naturally at room temperature to obtain a hydrophilic porous membrane; In the step S1, the mass fraction of the solvent is 48-85.5 parts, the mass fraction of the cross-linking agent is 0.5-5 parts, the mass fraction of the porogen is 2-10 parts, and the mass fraction of the membrane-forming polymer is 10-25 parts; The polyamine compound is any one of triethylenetetramine, tetraethylenepentamine, polyethylene polyamine, and polyethyleneimine polymer; the solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; the catalyst is any one of concentrated hydrochloric acid, concentrated sulfuric acid, or p-toluenesulfonic acid; the cross-linking agent is any one of glyoxal, glutaraldehyde, and epichlorohydrin; the porogen is any one of polyethylene glycol and polyvinyl pyrrolidone or a mixture of two of the two; and the membrane-forming polymer is any one of polyvinylidene fluoride, polyvinyl chloride, polysulfone, and polyether sulfone.

2. The preparation method according to claim 1, characterized in that: The volume of the catalyst accounts for 0-1% of the volume of the solvent.

3. The preparation method according to claim 1, characterized in that: In the step S1, the heating temperature is 60-80° C. and the cross-linking reaction time is 0.5-2 h.

4. The preparation method according to claim 1, characterized in that: In step S2, the coagulation bath is deionized water at 20-60°C.

5. A hydrophilic porous membrane, characterized in that: The preparation method is described in any one of claims 1 to 4.

6. The hydrophilic porous membrane according to claim 5, characterized in that The hydrophilic porous membrane is a flat membrane or a hollow fiber membrane.

Citation Information

Patent Citations

  • Preparation method for subject-object self-repairing transparent film

    CN106634586A

  • Cyclodextrin grafted halloysite nanotube organic solvent nanofiltration membrane and preparation method thereof

    CN111229059A